The midgut microbiota plays an essential role in sand fly vector competence for Leishmania major. (19th June 2017) - Louradour, Isabelle; Monteiro, Carolina Cunha; Inbar, Ehud; Ghosh, Kashinath; Merkhofer, Richard; Lawyer, Phillip; Paun, Andrea; Smelkinson, Margery; Secundino, Nagila; Lewis, Michael; Erram, Dinesh; Zurek, Ludek; et al.
Summary: For many arthropod vectors, the diverse bacteria and fungi that inhabit the gut can negatively impact pathogen colonization. Our attempts to exploit antibiotic treatment of colonized Phlebotomus duboscqi sand flies in order to improve their vector competency for Leishmania major resulted instead in flies that were refractory to the development of transmissible infections due to the inability of the parasite to survive and to colonize the anterior midgut with infective, metacyclic stage promastigotes. The parasite survival and development defect could be overcome by feeding the flies on different symbiont bacteria but not by feeding them on bacterial supernatants or replete medium. The inhibitory effect of the dysbiosis was moderated by lowering the concentration of sucrose (<30% w/v) used in the sugar feeds to maintain the colony. Exposure of promastigotes to 30% sucrose was lethal to the parasite in vitro. Confocal imaging revealed that the killing in vivo was confined to promastigotes that had migrated to the anterior plug region, corresponding to the highest concentrations of sucrose. The data suggest that sucrose utilization by the microbiota is essential to promote the appropriate osmotic conditions required for the survival of infective stage promastigotes in vivo .